Menstrual cycle-related fluctuations in oxytocin concentrations: a systematic review and meta-analysis - Engel, Sinha; Ditzen, Beate (Frontiers in neuroendocrinology, 2019)
Oxytocin affects physiological and psychological functions that are often expressed sex-specifically, suggesting interactions between oxytocin and sex hormones. As female sex hormone concentrations change during the menstrual cycle, oxytocin might fluctuate, too. This systematic review and meta-analysis investigated endogenous oxytocin concentrations across menstrual cycle phases in healthy women. Data from 13 studies (120 women) showed a significant increase of oxytocin concentrations from the early follicular phase to ovulation (g=0.39 [0.25; 0.53], p<.001) and a significant decrease from ovulation to the mid-luteal phase (g=−0.50 [−0.81; −0.18], p<.001). There were no significant differences between the early follicular and mid-luteal phase (g=−0.19 [−0.70; −0.32], p=.471). These findings contribute to a deeper understanding of differences in normal and abnormal psychobiological processes in women. They highlight the necessity to consider the menstrual cycle phase in studies on oxytocin in women.